2017
DOI: 10.1111/1467-8551.12217
|View full text |Cite
|
Sign up to set email alerts
|

Examining Facilitative Configurations of Entrepreneurially Oriented Growth: An Information Processing Perspective

Abstract: This study examines how the relationship between entrepreneurial orientation and firm growth is shaped by learning orientation in technologically sophisticated environments. We draw upon an information processing perspective that emphasizes alignment between information processing demands and support mechanisms. Using data from 116 small to medium‐sized enterprises in the Netherlands, we observe that the ability of entrepreneurial orientation to drive firm growth greatly depends on the joint consideration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 111 publications
0
22
0
Order By: Relevance
“…We show that the moderating effect of OO on the relationship between EO and resource acquisition changes between a high dynamic environment and a low dynamic environment. Configurational studies of EO have sought to answer the question why scholars have observed different results in the contribution of EO to outcomes important for new ventures Kearney, Soleimanof, & Wales, 2018). We provide new insight into when and why EO is especially beneficial for new ventures or when its effects may be lost, locating the matter to the degree of environmental dynamism.…”
Section: Contributionsmentioning
confidence: 92%
“…We show that the moderating effect of OO on the relationship between EO and resource acquisition changes between a high dynamic environment and a low dynamic environment. Configurational studies of EO have sought to answer the question why scholars have observed different results in the contribution of EO to outcomes important for new ventures Kearney, Soleimanof, & Wales, 2018). We provide new insight into when and why EO is especially beneficial for new ventures or when its effects may be lost, locating the matter to the degree of environmental dynamism.…”
Section: Contributionsmentioning
confidence: 92%
“…To date, prior research has prioritized (almost exclusively) family-oriented variables as contingencies (see Table 4 in Hernández-Linares and López-Fernández, 2018, for a comprehensive illustration). Instead, grounding ourselves in the contingency perspective of EO (Kearney et al, 2018) and resource orchestration theory (Sirmon et al, 2007(Sirmon et al, , 2011, we anticipate that strategy variables explain when (mediating) and knowledge management variables explain to what extent (moderating) EO dimensions affects family firm performance.…”
Section: Entrepreneurial Orientation and Family Firm Performancementioning
confidence: 99%
“…To answer these research questions, we use the contingency perspective of EO (Kearney et al, 2018;McKenny et al, 2018) together with resource orchestration theory (Sirmon et al, 2007;Sirmon et al, 2011). We test our thesis against a dataset of 268 Malaysian family firm s in a resource-scarce economy (Falahat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Equifinality theorists acquiesce to configuration theory and confer the presence of equifinal configurational paths of conditions that may exist as multiple routes to the desired outcome (Drazin & Van De Ven, 1985;Meyer et al, 1993). Entrepreneurial studies suggest that the assumption of equifinality can produce a more meaningful, productive and context-specific business model to determine firm performance (Kearney et al, 2018). Interactions among strategic actions and determinants to firms' performance are more appealing than direct causal effects.…”
Section: Foreign Market Knowledgementioning
confidence: 99%
“…However, most of the studies are firmly based on the contingent theoretical approach of FMK (Mostafiz et al, 2019a), which avoids the assumption of equifinality (Ragin, 2009). The contingent theory proposes the contextual solution for antecedents or determinants to achieve firm performance (Kearney et al, 2018). Based on this assumption, important antecedent or determinant often gets omitted.…”
Section: Introductionmentioning
confidence: 99%